Effect of the probiotic additive Bacillus subtilis and their endospores on milk production and immune response of lactating sows - Ayala, Lazara; Bocourt, R.; Castro, M.; Martínez, Mayuly; Herrera, Magaly (Cuban Journal of Agricultural Science, 2016)
Forty eight Yorkshire-Landrace x L35 were used with a range between three and five farrowings for determining the effect of the probiotic additive of Bacillus subtilis and their endospores on milk production and immune response of lactating sows. Experimental treatments were: control without additive; three weeks of probiotic consumption (G-3), consumption for four weeks (G-4), before farrowing and during the 33 d of lactation. Indicators evaluated maintained in the normal parameters, according to the species and animal category. Total protein differed between the control without additive and the G-3 (69.63, 77.56 and 74.86 g/L-1 for the control, G-3 and G-4, respectively), while for immunoglobulin concentration there was a significant increase between treated animals regarding the control (2.46, 2.84 and 2.89 g/L-1 for the control, G-3 and G-4, respectively). In a similar way performed milk production at 7, 21 and 28 d. Results suggest the possibility of supplying the additive without worsening the productive performance, with positive influence on the sow’s health. Key words: Bacillus subtilis, sows, health, milk production